Comparing Online and Offline Knowledge Networks of Carbon Capture and Storage. (July 2017) - Mander, Sarah; Cunningham, Rebecca; Lever, Louise; Gough, Clair
Abstract: This paper examines the complex ecosystem of organisations involved in the proposed role out of carbon capture and storage (CCS) in the UK. Through analysis of interview and twitter data, it focuses on the flow of knowledge flows within online and offline networks, highlighting how in this case, CCS retains a niche audience, with communication and information flows concentrated with industry and stakeholder networks at a local and regional scale, as opposed to reaching broader national policy makers, and the wider publics. This brings a unique insight into the construction of networks across intersecting sectors of this critical technology and highlights how for successful implementation CCS, actors may need to reach out beyond their existing network.